Transcriptomic analysis reveals distinct mechanisms of carvone and lipopeptide crude extract from Bacillus velezensis JZ in the postharvest biocontrol of Alternaria alternata on strawberries - Lizhu Shao; Boyuan Zhang; Xueling Zhao; Yating Wang; Ziyu Wang; Miaomiao Yang; Zunzun Qi; Yuansen Hu; Na Liu; Peng Li; Li Zhang (Postharvest Biology and Technology, 2027)

Beyond salting-in: Activating myofibrillar proteins for high internal phase emulsions via a pH–ionic strength complementarity mechanism - Feiyu Zhang; Peng Wang; Weiyi Zhang; Yating Xiong; Zitong Dong; Guanghong Zhou; Xinglian Xu (Food Chemistry, 2026)

Microplastic removal in field-scale and in-situ water treatment systems: A systematic performance review - Asfandyar Shahab; Licheng Peng; Abubakr M. Idris; He Xiao; Tauseef Ahmad; Yating Luo; Michael S. Bank (Process Safety and Environmental Protection, 2026)

Green antimicrobial intervention during pre-cooling: ultrasound-enhanced lactic acid improves chicken meat quality — insights from molecular dynamics and volatile profiling - Tianran Huang; Yating Liu; Lingqi Li; Yujia Yang; Guiming Li; Lei Wang; Yu Huang; Mingye Wu; Guanghui Li; Qingyong Zhang; Huixiao Liu; Peng Wang (Food Research International, 2026)

Large zircon age spans reveal protracted assembly of Neoproterozoic Emeishan granitoids and crustal reworking, western Yangtze Block - Yating Xu; Peng Wu; Xiangpeng Wang; Yichao Wang; Ailing Xian (Acta Geochimica, 2026)

Deamidation suppresses myofibrillar protein low-ionic-strength assembly to preserve dispersibility and enable fisetin loading - Zhen Li; Zongyun Yang; Yating Liu; Yun Bai; Xinglian Xu; Peng Wang (Innovative Food Science & Emerging Technologies, 2026)

The Matthew effect of defects in microflowers CuS/carbon foam composite optimizes the dielectric response for high-performance microwave absorption - Weibin Deng; Tiehu Li; Arooba Kanwal; Hao Li; Alei Dang; Keke Li; Peng Chang; Rui Zhou; Shengtao Gao; Yating Zhang; Hongjing Wu (Chemical Engineering Journal, 2026)

DKK1 activated the NF-κB pathway by binding with CKAP4 to induce PASMC oxidative stress and promote pulmonary arterial hypertension - Shaojin Wang; Xiuyan Wang; Lili Miao; Yating Zhang; Peng Zhang (Genes & Genomics, 2026)

Myeloid PKM2 deficiency alleviates allergic airway inflammation and promotes macrophage efferocytosis via SLC13A3 - Lingli Chen; Yile Liu; Yating Chen; Yue Zhang; Lei Yu; Yantong Zhu; Wang Peng; Maolan Wu; Xiangrong Zheng (Inflammation Research, 2026)

Effects of excess curdlan on the localized phase separation and gel strength deterioration of myofibrillar protein under different ionic strengths evidenced by Df and microrheology - Yang Ye; Lingqi Li; Yating Xiong; Zongyun Yang; Zhen Li; Xinglian Xu; Peng Wang (Food Chemistry, 2026)

The dominant role of amylose content in regulating the multiscale structure of hydroxypropyl distarch phosphate for 3D printing ice cream - Minghao Xu; Yating Xu; Shengyang Ji; Yonghao Liu; Diyi Zhang; Lin Feng; Yinliang Wu; Peng Zhang; Jianfu Shen; Baiyi Lu (Food Hydrocolloids, 2026)

Directed charge transfer in a chitosan-citric acid/NH2-UiO-66 hybrid via an amide bond bridge for photocatalytic co-production of benzaldehyde and H2O2 - Yating Lu; Huixia Zhu; Yue Han; Yu Tian; Xiaoxia Liang; Dongyu Nie; Tingming Ye; Yixu Peng; Xia Yang (Chemical Engineering Journal, 2026)

Evolutionary pattern of liquid-liquid phase separation in amphiphilic molecular self-assembly during the natural aging process of strong-aroma Baijiu - Xinyue Jiang; Yating Shang; Rahimi Hajar; Heng Yang; Jiaxin Peng; Jianhui Li; Weimin Wang; Zhaoyong Zou; Yuqun Xie (Food Research International, 2026)

Optimization of extraction methods, component identification of bound polyphenols from sea-buckthorn pomace, and its ameliorative effects on oxidative stress in sleep-deprived mice - Jing Peng; Xin Li; Mingyou Yuan; Yating Tang; Tianyi Qiao; Jiaying Li; Haoyang Yu; Meng Zhang; Xiulian Li; Ying Lan (Food Chemistry, 2026)

7,8-Dihydroxyflavone ameliorates bone loss by regulating TRKB/AKT/FOXO3a pathway in a mouse model of alzheimer’s disease - Dong Liu; Xiaoxiong Li; Peng Shi; Wenjuan Hong; Jie Huang; Mingliang Hou; Linqiu Ma; Qirong Liao; Hongyan Yang; Xiaoyan Fu; Huadong Zhou; Jing Lu; et al. (Psychopharmacology, 2025)

The structural changes of Fisetin-Myofibrillar protein complexes induced by different non-covalent binding methods influence the adsorption of mucin glycoprotein: Spectroscopy, molecular docking and QCM-D - Zhen Li; Zongyun Yang; Yating Liu; Yun Bai; Xianming Zeng; Xincheng Mei; Xinglian Xu; Peng Wang (Food Bioscience, 2025)

Core–shell nanoparticle: curcumin-induced protein conformation changes enhance the adsorption of hyaluronic acid, as studied via spectroscopy, molecular dynamics simulation and energy dissipation - Zongyun Yang; Zhen Li; Fengnan Niu; Yating Liu; Yun Bai; Xinglian Xu; Peng Wang (Food Hydrocolloids, 2025)

Genomic and phenotypic analysis of virulence, antimicrobial resistance, and transmission routes of Vibrio vulnificus from food and clinical sources in China - Yating Xu; Ruanyang Sun; Zhiwei Zheng; Lianwei Ye; Mingxiu Peng; Sheng Chen (Food Research International, 2025)

Innovations in the meat colloid science: Exploring the future of meat from the perspectives of sustainability, health, and personalization - Zhen Li; Zongyun Yang; Yue Qi; Yun Bai; Xianming Zeng; Yating Liu; Xinglian Xu; Peng Wang (Food Research International, 2025)

Corrosion-resistant, biodegradable green coatings for automotive conductive primers - Yating Li; Xin Tian; Kexin Zhou; Junbo Wang; Chong Peng; Shuyi Yang; Tao E (Chemical Engineering Journal, 2025)

Non-alkaloidal constituents with chemotaxonomic value from Aconitum episcopale - Tianpeng Yin; Xiaojing Shen; Min Yan; Peng Yating (Biochemical Systematics and Ecology, 2025)

Targeted capture of Bacillus thuringiensis using phage endolysin cell wall binding domain with high recognition specificity - Qin Peng; Lushuang Wang; Gege Feng; Xi Chen; Dan Li; Yating Zeng; Yingqi Qian; Zhirou Sun; Yihui Yuan (Chemical Engineering Journal, 2025)

GhCTEF2 encodes a PLS-type PPR protein required for chloroplast development and plastid RNA editing in cotton - Huan He; Mengxue Cheng; Bowen Bao; Yanan Tian; Yating Zheng; Yuzhu Huo; Zengqiang Zhao; Zongming Xie; Jianing Yu; Peng He (Plant Science, 2025)

More than a thickener: guar gum affects PSE myosin emulsion stability through different modes by energy dissipation and molecular dynamic characterization - Zongyun Yang; Zhen Li; Peng Wang; Yun Bai; Yating Liu; Weinan Wang; Xinglian Xu; Juan Shen (Food Hydrocolloids, 2025)

Multi-omics analysis reveals the role of L-Glutamate in regulating cold tolerance of postharvest prune fruit - Yuanyuan Hou; Wanyu Yan; Rui Deng; Jiayi Wang; Yu Wang; Liang Wang; Jun Xing; Peng Jin; Yating Zhao (Postharvest Biology and Technology, 2025)

Nanocomposite hydrogel with multiple metal ions coupling for effective treatment of bacteria infected wound via cascade catalysis and tissue regeneration - Yating Liu; Wenyun Mu; Yu Wang; Tao Liu; Zhenzhen Peng; Xin Chen (Chemical Engineering Journal, 2025)

Growth Onset Rather Than Photosynthesis Strongly Regulates Autumn Senescence Termination Besides Climate Change - Shuping Ji; Shilong Ren; Yann Vitasse; Constantin M. Zohner; Yongshuo H. Fu; Xiaoqiu Chen; Xiaoyang Zhang; Charlotte Grossiord; Huiying Liu; Matthias Peichl; Dailiang Peng; Shuai An; et al. (Global Ecology and Biogeography, 2025)
Aim Plant senescence largely influences the global carbon cycle by regulating the growing season length. However, the driving mechanisms of plant senescence remain unclear, particularly the role of developmental factors. This study aims to investigate how environmental and developmental factors drive autumn senescence and evaluate whether woody and herbaceous plants exhibit divergent responses to these drivers. Location Eurasia. Time Period 1982–2014. Major Taxa Studied Woody and herbaceous species. Methods Using 120,833 long‐term ground phenological observations, we employed partial correlation analysis to investigate the influence of environmental and developmental factors on senescence termination. Experimental records from literature and pasture survey observations from China were separately utilised to further validate the influence of developmental factors on senescence termination. Structural equation modelling was applied to analyse the pathways of growth onset affecting senescence termination. Additionally, multiple linear regression was used to examine the tendency of the sensitivity of senescence termination to plant development rate. Results We find that earlier growth onset primarily leads to earlier senescence termination directly in herbaceous plants, but indirectly in woody plants by accelerating early‐season development. The sensitivity of senescence termination to plant development rate shows a declining trend, particularly in early‐season negative effects on woody plants and late‐season positive effects on herbaceous plants, suggesting diminished impacts of future warming on senescence timing. The impact of growing season photosynthetic activity on senescence termination is not pronounced for both woody and herbaceous plants. Main Conclusions The results demonstrate that growth onset may affect woody and herbaceous senescence termination through different pathways, whereas the carry‐over effects of growing season photosynthetic activity are not widely discovered. This emphasises that the introduction of developmental factors into phenological models needs to be considered carefully according to plant type.

The impact of the structural transformation mechanism of fulvic acid on redox capacity during composting with different biowastes - Chuanyan Zhang; Zhigang Yi; Xing Peng; Xinyu Zhao; Yating Chen; Beidou Xi (Environmental Research, 2025)

Transparent mechanism of salted egg (white) hierarchically and synergistically driven by NaCl, NaOH and thermal treatment: Based on empirical data and molecular simulation - Le Chen; Shiqin Dong; Peng Xu; Zhuosi Yu; Yating He; Yongle Liu; Xiaole Xiang; Qun Huang; Shugang Li; Lin Ye (Food Chemistry, 2025)

Chinese advances in understanding and managing genitourinary tract infections caused by Mycoplasma genitalium, Mycoplasma hominis, and Ureaplasma urealyticum - Yanyan Qiu; Siyi Mao; Xianqi Li; Yinan Chen; Wenxin Chen; Yating Wen; Peng Liu (Archives of Microbiology, 2025)

Contrasting orbital rhythms preserved in loess grain-size records across the Chinese Loess Plateau - Deai Zhao; Guoqiao Xiao; Chunju Huang; Haibin Wu; Qingzhen Hao; David B. Kemp; Shaohua Tian; Zhipeng Wu; Hao Lu; Gaowen Dai; Shuzhen Peng; Changyan Tang; et al. (Global and Planetary Change, 2024)

L-Glutamate treatment alleviates chilling injury of prune (Prunus domestica L.) fruit by regulating ROS homeostasis, GABA shunt, and energy metabolism - Yuanyuan Hou; Rui Deng; Dilireba Shataer; Jingyang Hong; Liang Wang; Peng Jin; Yating Zhao (Food Chemistry, 2024)

Perioperative complications of middle cerebral artery occlusion in rats alleviated by human umbilical cord mesenchymal stem cells - Liang Liu; Yating Luo; Tao Xu; Qisheng Tang; Jialian Yi; Linping Wang; Shixiang Luo; Zhaohong Bi; Jianlei Liu; Jun Lu; Weiwei Bi; Changguo Peng; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Exploring a specialized programmed-cell death patterns to predict the prognosis and sensitivity of immunotherapy in cutaneous melanoma via machine learning - Leyang Xiao; Ruifeng He; Kaibo Hu; Gelin Song; Shengye Han; Jitao Lin; Yixuan Chen; Deju Zhang; Wuming Wang; Yating Peng; Jing Zhang; Peng Yu (Apoptosis, 2024)

Enhancing antitumor efficacy of NIR-I region zinc phthalocyanine@upconversion nanoparticle through lysosomal escape and mitochondria targeting - Qiuhao Ye; Jiao Wang; Ruotao Guo; Guizhi Chen; Yating Shen; Yijin Wu; Jingtang Wang; Zeyu Lin; Kun Wang; Jianling Chen; Yiru Peng (Journal of Photochemistry and Photobiology B: Biology, 2024)

Long-Term Spatiotemporal Characteristics of Ulva prolifera Green Tide and Effects of Environmental Drivers on Its Monitoring by Satellites: A Case Study in the Yellow Sea, China, from 2008 to 2023 - Yating Zhan; Zhongfeng Qiu; Yujun Wang; Yiming Su; Yin Li; Yanmei Cui; Shuai Qu; Peng Wang; Xin Rong (Journal of Marine Science and Engineering, 2024)
Ulva prolifera (U. prolifera) green tide outbreaks have occurred in the Yellow Sea of China for many years, causing serious losses to marine ecology and the marine economy. The monitoring and tracking of U. prolifera green tide is a crucial aspect of marine ecological disaster prevention and control management. This paper aims to investigate the spatiotemporal distribution changes in U. prolifera green tide in the Yellow Sea throughout its life cycle. A survey of the Yellow Sea from 2008 to 2023 was conducted using multi-source remote sensing images. Long-term monitoring and analysis of U. prolifera revealed the evolution process of the green tide, including the early development, outbreak, decline, and extinction stages, considering time, space, and frequency of occurrence. Additionally, this study examined peak coverage change patterns over the past 16 years and analyzed the influence of environmental factors such as sea surface temperature and sea surface wind field on the development of U. prolifera. The research results serve as a valuable reference for the monitoring, early warning, and scientific prevention and control of U. prolifera green tide in the Yellow Sea, as well as other similar marine disaster areas.

Predicting low carbon pathways on the township level in China: a case study of an island - Yating Zhao; Yahong Dong; Peng Liu (Environmental Monitoring and Assessment, 2024)

Lithium Chloride Promotes Endogenous Synthesis of CLA in Bovine Mammary Epithelial Cells - Jiayi Liu; Jinglin Shen; Jinxin Zong; Yating Fan; Junhao Cui; Dongqiao Peng; Yongcheng Jin (Biological Trace Element Research, 2024)

Saccharin copolymerization-modified metal-free graphite carbon nitride for efficient photocatalytic removal of tetracycline hydrochloride in actual water samples: Process and mechanism - Yating Wang; Airu Liu; Chaosheng Peng; Jinyue Song; Xingang Li; Zhenxue Liu; Tao Jiang (Journal of Environmental Chemical Engineering, 2023)

Multi-USV cooperative path planning by window update based self-organizing map and spectral clustering - Peng Yao; Yating Lou; Keming Zhang (Ocean Engineering, 2023)

Alpine-style tectonic nappe stacking in an Archean suture zone: Quantitative structural profile places constraints on orogenic architecture - Yating Zhong; Timothy M. Kusky; Lu Wang; Chuanhai Wang; Yaying Peng; Tingting Wang; Chao Yan (Gondwana Research, 2023)

Hippocampal Iron Accumulation Impairs Synapses and Memory via Suppressing Furin Expression and Downregulating BDNF Maturation - Yating Zhang; Xue Bai; Yi Zhang; Shanshan Yao; Yiduo Cui; Lin-Hao You; Peng Yu; Yan-Zhong Chang; Guofen Gao (Molecular Neurobiology, 2022)

Inhibitory mechanism of angiotensin-converting enzyme inhibitory peptides from black tea - Yating Lu; Yu Wang; Danyi Huang; Zhuang Bian; Peng Lu; Dongmei Fan; Xiaochang Wang (Journal of Zhejiang University-SCIENCE B, 2021)

Effects of a conversion from grassland to cropland on the different soil organic carbon fractions in Inner Mongolia, China - Yuchun Qi; Yunshe Dong; Qin Peng; Shengsheng Xiao; Yating He; Xinchao Liu; Liangjie Sun; Junqiang Jia; Zhijie Yang (Journal of Geographical Sciences, 2012)

Soil nitrous oxide emissions from a typical semiarid temperate steppe in inner Mongolia: effects of mineral nitrogen fertilizer levels and forms - Qin Peng; Yuchun Qi; Yunshe Dong; Shengsheng Xiao; Yating He (Plant and Soil, 2011)

Spatial-temporal variation in soil respiration and its controlling factors in three steppes of Stipa L. in Inner Mongolia, China - YuChun Qi; YunShe Dong; LiXin Liu; XingRen Liu; Qin Peng; ShengSheng Xiao; YaTing He (Science China Earth Sciences, 2010)